DETERMINANT OF LOYALTY OF EXECUTIVE CLASS PATIENTS AT AMBULATORY SERVICES AT SILOAM HOSPITALS TB SIMATUPANG DURING COVID-19 PANDEMICS - Sembiring, Dian Agnesa; Nurwahyuni, Atik (Journal of Indonesian Health Policy and Administration, 2023)
Business competition in the health industry is getting tighter, especially since the COVID-19 pandemic has significantly decreased patient visits. This study aims to determine the determinants of executive patient loyalty at the Siloam Hospitals TB Simatupang outpatient installation during the COVID-19 pandemic era. This research is quantitative research with an observational research design. The study population consisted of 520 patients with a sample of 84 patients with research instruments using a questionnaire. The results of the study stated that most respondents were loyal to services at the executive clinic, with an NPS of 50%. Customer satisfaction, service quality, perceived value, trust, hospital brand image, and commitment significantly and positively affect executive patient loyalty. Specifically, the commitment variable has a direct influence on loyalty. Customer satisfaction, service quality, trust, hospital brand image, and OCB indirectly affect loyalty. Commitment (0.865) is the most influential variable on patient loyalty. Furthermore, the variables customer satisfaction (0.541), trust (0.484), service quality (0.425), OCB (0.249), hospital brand image (0.107) respectively also have a degree of influence on patient loyalty.